Identifying and Spurring High-Growth Entrepreneurship : Experimental Evidence from a Business Plan Competition - McKenzie, David (World Bank, Washington, DC, 2015)
Almost all firms in developing countries have fewer than 10 workers, with the modal firm consisting of just the owner. Are there potential high-growth entrepreneurs with the ability to grow their firms beyond this size? And, if so, can public policy help alleviate the constraints that prevent these entrepreneurs from doing so? A large-scale national business plan competition in Nigeria is used to help provide evidence on these two questions. The competition was launched with much fanfare, and attracted almost 24,000 entrants. Random assignment was used to select some of the winners from a pool of semi-finalists, with US$36 million in randomly allocated grant funding providing each winner with an average of almost US$50,000. Surveys tracking applicants over three years show that winning the business plan competition leads to greater firm entry, higher survival of existing businesses, higher profits and sales, and higher employment, including increases of over 20 percentage points in the likelihood of a firm having 10 or more workers. These effects appear to occur largely through the grants enabling firms to purchase more capital and hire more labor.